2021
DOI: 10.1002/nop2.1116
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between paediatric nurses' quality of life and intent to leave: The moderating role of hospital type

Abstract: Nursing is one of the most stressful professions that affect nurses' quality of life (QOL) negatively (Kandi & Zeinali, 2017) and increase their intent to leave (ITL) the job (Andresen et al., 2017).QOL is a general term that was defined by the world health organization (WHO) as the perceived evaluation of own life surrounded by a cultural, social and environmental framework (World Health Organization, 1996). So, nurses' QOL reflects their well-being and affects their productivity. ITL means having or making a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…These factors have been associated with the attractiveness of nursing and nurse retention earlier. [28,31] As earlier research, [7,10] this study also highlights the importance of a fair salary to attract a new workforce. The issue of fair compensation concerns many other healthcare professions as well.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These factors have been associated with the attractiveness of nursing and nurse retention earlier. [28,31] As earlier research, [7,10] this study also highlights the importance of a fair salary to attract a new workforce. The issue of fair compensation concerns many other healthcare professions as well.…”
Section: Discussionsupporting
confidence: 81%
“…[7] Dissatisfaction with salary has also been reported in many other countries. [10] The negative impact of a poor work environment has been documented several times over the years. [11] Factors that have been found to decrease commitment and attractiveness of the profession include limited opportunities for professional development, [12] as well as an unhealthy working environment and bullying, [13] and poor management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies (Haun & Baethge, 2020; Hulsegge et al., 2020; Khatatbeh et al., 2022; Khatatbeh, Pakai, et al., 2021; Khatatbeh, Pakai, Pusztai, et al., 2020; Khatatbeh, Pakai, Zrínyi, et al., 2020; Khatatbeh, Alhalaiqa, et al., 2021; Khatatbeh, Al‐Maqableh, et al., 2021; Khatatbeh, Khasawneh, et al., 2021; Nabe‐Nielsen et al., 2011), we hypothesized that paediatric nurses' burnout and their perceived health are correlated and that the common work‐shift moderates this relationship (See Figure 1). Up to our knowledge, this study is the first of its type to study the moderating effect of work‐shift in the relationship between nurses' burnout and their perceived health.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of recent events, Naghizadeh et al reported a reverse correlation between fears of COVID-19 and QOL. 9 The patient’s QOL is closely related to various factors such as the intent to leave, 10 stress, marital relationship, 11 psychosocial processes, 12 provider communication behaviors, 13 and care burden. 14 For HIV patients, Liu et al’s study found that the sexual orientation was closely related to the QOL of HIV patients in China, and a better QOL was found for homosexual individuals (34028639).…”
Section: Introductionmentioning
confidence: 99%